Project 30 Program
About the Project 30 Program of USATF, which is a cooperative venture with Nike and which is designed to assist emerging elite and elite athletes to stay in the sport of track & field at critical periods in their athletic careers. The primary goal of the program is to help immediate and recent post-collegians "bridge the gap" experienced by many top college athletes after completing their collegiate eligibility. The secondary goal will be to assist veteran, elite athletes who warrant consideration for the program due to special circumstances in their athletic careers and/or lives.